FRI0367 INFLAMMATORY PROCESSES IN EXPERIMENTAL SPONDYLOARTHRITIS ARE ACCOMPANIED BY FORMATION OF ECTOPIC LYMPHOID STRUCTURES IN THE BONE MARROW AND ALTERATIONS IN THE B CELL LINEAGE. (June 2019) - Kaaij, Merlijn; Hamburg, Jan Piet van; Rip, Jasper; Kollias, George; Baeten, Dominique; Nolte, Martijn; Duivenvoorde, Leonie van; Tas, Sander W.
Abstract : Background: Tumour necrosis factor (TNF) is important in immune-mediated inflammatory diseases such as spondyloarthritis (SpA). SpA patients have extensive angiogenesis in inflammatory and bone forming regions. Transmembrane (tm)TNF-transgenic (tg) mice (1) that overexpress tmTNF develop SpA symptoms, including inflammation, bone destruction and bone formation. Interestingly, these mice also develop lymphoid aggregates in the bone marrow (BM) of the axial and peripheral skeleton. Objectives: Characterization of lymphoid aggregates in tmTNF tg mouse BM in the context of angiogenesis and bone formation. Methods: Ankles, femora, tibiae, vertebrae and spleens from tmTNF tg mice and wild-type (WT) littermates (6 weeks, 12 weeks, and 8 months old; n=5 per age per group) were dissected and analyzed by confocal microscopy. In addition, 12 week old mice (n=5 per group) were analyzed by flow cytometry. To study the importance of TNF-R signaling in these processes, tmTNF tg mice lacking TNF-RI (tmTNF tgxTNF-RI -/- ) or TNF-RII (tmTNF tgxTNF-RII -/- ) (n=4 per group) were investigated. Results: Immunofluorescent (IF) evaluation demonstrated that BM of tmTNF tg mice contained extensive lymphoid aggregates, both in the vertebrae and the ankles, but not in the femurs or spleen. IF microscopy demonstrated that the aggregates in the BM contain characteristics of ectopic lymphoid structures (ELS) and consisted of B220 + B cells and FDC-M1 + follicular dendritic cells that are in close proximity of MECA79 + high endothelial venules (HEVs). Flow cytometric analysis revealed that most B220 + B cells are IgD + naive B cells and that tmTNF tg vertebrae contain significantly more IgD - CD95 + germinal center B cells (P< 0.01) with a higher expression of the costimulatory molecules CD80 and CD86 compared to WT. The vertebrae also contained more CXCR5 + PD-1 + FoxP3 + CTLA4 + T regulatory cells and a trend towards an increase in CXCR5 + PD-1 + FoxP3 - CTLA4 - T follicular helper cells in tmTNF tg mice. Meanwhile, B cell development in the BM of tmTNF tg hind limbs was not altered. Furthermore, BM, spleen and vertebrae from tmTNF tg mice contained significantly more IgA + plasma cells compared to WT littermates. Of note, tmTNF tgxTNF-RI -/- mice did not display lymphoid aggregates or HEVs in the BM, while tmTNF tgxTNF-RII -/- mice did, although to a lesser extent than tmTNF tg mice. Conclusion: tmTNF overexpression in mice results in extensive lymphoid aggregates in the BM that are often organized in ELS, which may be mediated via TNF-RI signaling. These ELS might result in an increase of IgA + plasma cells in tmTNF tg mice. Ongoing studies will look further into this and may indicate whether these findings contribute to the pathology observed in these mice. Reference: [1] Alexopoulou L, et al. Eur J Immunol1997; 27(10):2588-92 Disclosure of Interests: Merlijn Kaaij: None declared, Jan Piet van Hamburg: None declared, Jasper Rip: None declared, George Kollias: None declared, Dominique Baeten Employee of: UCB Pharma, Martijn Nolte: None declared, Leonie van Duivenvoorde: None declared, Sander W. Tas: None declared